2013
DOI: 10.1038/aps.2013.104
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and bioassay of β-(1,4)-D-mannans as potential agents against Alzheimer's disease

Abstract: Synthetic homogeneous short chain β-(1,4)-D-mannans shows neuroprotective effect against Aβ peptide toxicity similar to that of heterogeneous oligomannurarate 971 and alzhemed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…We realized that our analysis was exploratory and did not survive multiple comparison correction; thus, our ndings should be interpreted with caution. 18 F-FDG-PET data showed that treatment with GV-971 at 900 mg/day slowed the impairment of cerebral glucose metabolism in several AD-associated brain regions. Our results imply that the effects of GV-971 on neuronal function are not simply compensatory in the brain regions affected by AD.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…We realized that our analysis was exploratory and did not survive multiple comparison correction; thus, our ndings should be interpreted with caution. 18 F-FDG-PET data showed that treatment with GV-971 at 900 mg/day slowed the impairment of cerebral glucose metabolism in several AD-associated brain regions. Our results imply that the effects of GV-971 on neuronal function are not simply compensatory in the brain regions affected by AD.…”
Section: Discussionmentioning
confidence: 97%
“…All results have been expressed as least squares adjusted means and 95% CI. Finally, subjects in the cerebral 18 F-FDG-PET small subgroup underwent PET scanning at baseline and week 24. The relative cerebral metabolic rate for glucose was calculated as the standardized uptake value ratio for the brain regions known to be affected by AD, with the whole brain serving as the reference region.…”
Section: E Cacy Endpoints and Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…With studies continuing to explore the structure-based mechanisms of action of JG6, it is hoped that these results will add impetus to the search for cofilin-targeted carbohydrate-based anti-cancer agents. Our study provides important insights into oligosaccharides as a new and hitherto unrecognized therapeutic class[36]. The unique affinity to proteins of this class of compounds may open new therapeutic opportunities, in particular for those targets challenging to access by small-molecule inhibitors.…”
Section: Discussionmentioning
confidence: 99%